Effective dispersion of graphene nanoplatelets in epoxy grout for pipeline rehabilitation - Lim, Kar Sing; Kasmaon, Ain Shahira; Chin, Siew Choo; Doh, Shu Ing (AIP Publishing, 2018)
After years of operation, oil and gas pipelines are subjected to various damage mechanisms such as third party damage, material defect, and corrosion. These damaged pipelines need to be repaired/rehabilitated to ensure safe operation in the future. Nowadays, numerous rehabilitation techniques and repair methods are available for onshore and offshore pipelines including the usage of Fibre-Reinforced Polymer composite. A composite repair system consists of three parts which are composite wrapper, adhesive and infill materials and it is the most preferable techniques in repairing damaged pipeline in oil and gas industry. High strength infill materials has the potential in improving overall repair performance of composite repair system. The purpose of this research is to investigate the effectiveness of graphene nanoplatelets as reinforcement to enhance the mechanical properties of epoxy grout used as infill materials by adding 0.01%, 0.05% and 0.1% of graphene nanoplatelets. The dispersion was done by calendaring technique using a three-roll mill machine where the graphene particles were de-agglomerated to achieve homogenous dispersion. The results of tensile and compression tests show increment of strength for all graphene-modified samples. The strength increment was recoded range from 23% to 50% and 9% to 22% under tensile and compression test, respectively. The highest tensile strength was recorded at 20.89 MPa for sample with 0.1% graphene while sample with 0.05% graphene shows 82.67 MPa in compressive strength. This signifies the effectiveness dispersion of graphene nanoplatelets as reinforcement in the epoxy grout. As a conclusion, graphene nanoplatelets has great potential to improve the mechanical properties of epoxy grout with the aid of proper dispersion process.